Resolving the Two “Bony” Faces of PPAR-γ - Beata Lecka-Czernik; Larry J. Suva (PPAR Research)
Bone loss with aging results from attenuated and unbalanced bone turnover that has been associated with a decreased number of bone forming osteoblasts, an increased number of bone resorbing osteoclasts, and an increased number of adipocytes (fat cells) in the bone marrow. Osteoblasts and adipocytes are derived from marrow mesenchymal stroma/stem cells (MSC). The milieu of intracellular and extracellular signals that controls MSC lineage allocation is diverse. The adipocyte-specific transcription factor peroxisome proliferator-activated receptor-gamma (PPAR-γ) acts as a critical positive regulator of marrow adipocyte formation and as a negative regulator of osteoblast development. In vivo, increased PPAR-γ activity leads to bone loss, similar to the bone loss observed with aging, whereas decreased PPAR-γ activity results in increased bone mass. Emerging evidence suggests that the pro-adipocytic and the anti-osteoblastic properties of PPAR-γ are ligand-selective, suggesting the existence of multiple mechanisms by which PPAR-γ controls bone mass and fat mass in bone.